Nursing Care for elderly with Osteoarthritis: Red Ginger Warm Compress Intervention - Rizkianto, Dendi; Alfiansyah, Rudy; Wahyudin (CV. Literasi Publikasi Indonesia, 2025)
The elderly are a population group aged 60 years or older. An elderly person usually experiences several changes, namely physical, mental, social, and spiritual changes. Osteoarthritis (OA) is a long-term chronic disease characterized by the degeneration of joint cartilage, which causes bones to rub against each other and triggers stiffness, pain, and disturbances in daily movements. The complications that arise depend on the location of the joint experiencing OA and how the repair process occurs during therapy. Treatment to reduce the pain experienced can be done by non-pharmacological methods, such as red ginger warm compress therapy. Purpose: This case study aims to provide an overview of the application of red ginger warm compress therapy as an intervention for osteoarthritis patients with musculoskeletal system disorders. Method: The method used is a descriptive case study by conducting anamnesis, observation, physical examination, and medical record reviews, as well as analyzing the theoretical and practical aspects of nursing care provided based on evidence-based practice (EBP). Participants in this study were osteoarthritis patients who received warm red ginger compress therapy. Results: The results of a case study on osteoarthritis patients with chronic pain nursing problems showed that these problems could be overcome by performing red ginger warm compress therapy. This was indicated by the client experiencing a decrease in the pain scale. Therefore, red ginger warm compress therapy has been empirically proven as a chronic pain intervention for osteoarthritis patients in the Kenanga Griya Elderly Room, Garut Regency. Thus, it can be concluded that warm red ginger compress therapy has an effect on pain in osteoarthritis patients in the Kenanga Griya Elderly Room, Garut Regency. Conclusion: Red ginger warm compress therapy can be applied in providing nursing care to the elderly with osteoarthritis because it is effective in reducing pain.